ORGANIZATIONAL FACTORS INFLUENCING THE GROWTH OF YOUTH OWNED ENTERPRISES AS MODERATED BY GOVERNMENT POLICIES IN KABARNET TOWN, BARINGO COUNTY - Cherop, Gabriel Kipruto (IJRDO - Journal of Business Management, 2019)
Youth enterprise is the application of entrepreneurial skills, innovation and creativity into the world of business. In Kenya many youth enterprises continue facing many challenges due to ineffective promotion mechanisms. The purpose of the study was to establish the organizational factors influencing growth of YOEs (YOEs) in Baringo County. The objectives of the study were to explore the influence of financial support on the growth of YOEs; determine the influence of entrepreneurship training on the growth of YOEs; determine the influence of information communication technology on the growth of YOEs and to establish the influence of government policies on the growth of YOEs in Baringo County. The study was guided by two theories namely the resource based theory and the human capital theory. The study employed the descriptive research design. The study population comprised of 270 YOEs operators in Kabarnet town, Baringo County. Stratified random sampling was applied in selecting the sample size. A sample size of 73 respondents was determined using Yamane’s formula. Primary data was collected using questionnaire. Quantitative data was analyzed using descriptive statistics and inferential statistics based on the study’s objectives. Frequency tables, figures and charts were used to represent the results and the study findings. Based on the study findings, the study concludes that there was a positive relationship between financial support and growth of YOEs in Kabarnet town. It is also concluded that entrepreneurial training such as business seminars and workshops influenced youth awareness on how to improve performance of their businesses; hence, there was a positive relationship between entrepreneurship training and the growth of YOEs. The study also concludes that the growth of YOEs depended on favourable policies such as taxation, patenting laws and licensing regulations on YOEs. It is also concluded that the internet connection helped many youth businesses to enhance their success. Hence, there was a positive relationship between information communication technology and growth of YOEs in Kabarnet town. Generally, the study concludes that financial support, entrepreneurship training, information communication technology and government policies accounted for the variance in the growth of YOEs in Kabarnet town. The study recommends that financial support programmes should be redesigned to overcome the weaknesses that hinder their accessibility by the youth. The government should also relax rules regarding business policies aimed at supporting youth businesses. Entrepreneurship training programmes should be rolled out mostly for the youths to equip the youth with skills to run their own enterprises.